THE IMPLEMENTATION OF PPKN LEARNING PROCESS IN DEVELOPING STUDENT DEMOCRATIC VALUES CLASS XI MIA 2 SMA LABSCHOOL UNTAD PALU - Utami Nur Malida (Education Journal, 2020)
The objectives of this study were (1) to see the implementation of the PPKn learning process in fostering democratic attitudes of students in class XI MIA 2 SMA Labschool UNTAD Palu; (2) the impact of the impact of the PPKn learning process on the behavior and attitudes of class XI MIA 2 SMA Labschool UNTAD Palu. This type of research is qualitative research with a qualitative descriptive approach. The unit of analysis in this study was students of class XI MIA 2 as well as the subject. The informants were 1 PPKn teacher and 8 students of class XI MIA 2 with purposive sampling technique. The data techniques used were observation, interviews, questionnaires and documentation. The results showed that the implementation of the PPKn learning process in fostering democratic attitudes of class XI MIA 2 students was carried out through two strategies. First, through learning materials to behave politely in democratic Pancasila in accordance with the 1945 Constitution of the Republic of Indonesia. Second, through various learning methods, methods of discussion, sermons and question and answer, and the media used by whiteboards, worksheets and module books, from the application The PPKn teacher gave students to make students behave more politely in accordance with Pancasila and the 1945 Constitution. The impact of the PPKn learning process on the behavior and democratic attitudes of class XI MIA 2 students, namely students becoming more tolerant, respectful, free to express opinions, open and communication, as well as upholding togetherness between students with each other. It can be perfected that the implementation of the PPKn learning process in fostering democratic values ​​of class XI MIA 2 students at SMA Labschool UNTAD Palu can be accepted by all students which can be seen from the student's behavior that reflects democratic values ​​both in class and outside the classroom.